Bridging the humor barrier humor competency training in English language teaching - Rucynski, John, Jr; Prichard, Caleb; Pomerantz, Anne; Winchester, Jules; Ramirez de Arellano, Maria; Heidari-Shahreza, Mohammad Ali; Gardner, Scott; Pimenova, Nadezda; Hodson, Richard; Petkova, Maria (Lexington Books, 2020)
Humor competence in the target language is an overlooked tool for English language learners to communicate confidently and proficiently in English. In this innovative edited collection, language teachers and researchers from around the globe share their latest research on helping learners to overcome the humor barrier.